Cationic Aerosol Photopolymerization. Issue 2 (29th September 2014) - Akgün, Ertan; Muntean, Alex; Hubbuch, Jürgen; Wörner, Michael; Sangermano, Marco
Abstract Photoinitiated polymerization in aerosols is employed for the preparation of spherical polymer particles via cationic polymerization. The UV irradiation of aerosol monomer droplets starts the cationic curing process without the employment of any solvent or additives such as stabilizers, resulting in highly pure polymers. Crosslinked polymer spheres with a high gel content are obtained by processing vinyl ether and epoxy monomers via this aerosol‐photopolymerization technique, which exhibits great potential for the development of multifunctional materials.<inline-graphic xlink:href="ark:/27927/pgjf867kkr" content-type="mame201400211-gra-0001" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />